Relation between chloride secretion and intracellular cyclic adenosine monophosphate in a cloned human intestinal cell line HT-29 cl 19A. Issue 5 (May 1994) - Nath, S K; Huang, X; L'helgoualc'h, A; Rautureau, M; Bisalli, A; Heyman, M; Desjeux, J F
Abstract : The relation between the intracellular cyclic adenosine monophosphate (cAMP) content and the electrogenic chloride secretion induced by cholera toxin was studied in secretory HT-29 cl 19A cell monolayers. Cells were treated by the mucosal addition of cholera toxin (5 micrograms/ml) for 10, 45, or 90 minutes in Ussing chambers. After 10 minutes, the mean (SEM) intracellular cAMP content (3.2 (0.2) pmol/mg protein) and short circuit current (Isc) (1.9 (0.3) microA.cm-2) did not differ significantly from the corresponding basal values. At 45 minutes, a significant increase in the Isc (22.2 (5.7) microA.cm-2) was accompanied by a significant elevation in cAMP (10(1.7) pmol/mgh protein). At 90 minutes, when the stimulated Isc plateaued (35.2 (5.2) microA.cm-2), the cAMP value (99.2 (23.8) pmol/mg protein) increased further. The protein kinase C (PKC) activity of the cells was not affected by cholera toxin. Treatment of cell monolayers by different concentrations of DbcAMP (10(5), 5 x 10(-5), 10(-3) M) showed that the minimal concentration of DbcAMP (serosal) which significantly increased the Isc (delta 4.5 microA.cm-2) was 10(-4) M, and that this was accompanied by an increase in cAMP of delta 6.7 pmol/mg protein: Compared with DbcAMP, cholera toxin stimulated the Isc (at 45 minutes) to a much higher degree with a comparable elevation of cAMP. It is concluded that in cl 19A cells there is a threshold value of increase in intracellular cAMP that induces chloride secretion. Cholera toxin stimulated chloride secretion can be explained predominantly by an increase in intracellular cAMP that is unrelated to PKC activity.